DETERMINANT FACTORS OF LECTURER PERFORMANCE AT THE RESIDENCE OF PEKALONGAN - Wartulas, Sri; Sugiyo; Sudana, I made; Suminar, Tri (CENTRAL ASIA AND THE CAUCASUS, 2022)
Lecturer performance is basically the performance or performance carried out by lecturers in carrying out their duties as educators. The quality of educational outcomes is highly dependent on the quality of lecturer performance. The purpose of this study is to develop an empirical model to improve lecturer performance. The development of the model as an alternative construct that is thought to be able to color the influence of transformational leadership, organizational culture, organizational commitment on lecturer performance through achievement motivation. Furthermore, achievement motivation will mediate the influence of transformational leadership, organizational culture, organizational commitment on lecturer performance. The independent variables of the study consist of transformational leadership, organizational culture and organizational commitment while the mediating variable is achievement motivation) and the dependent variable is lecturer performance, which is a quantitative study using path analysis. The research population is lecturers from 17 private universities in Pekalongan Residency, totaling 789 people. The research sample was 258 people using the proportional cluster random sampling technique. The results of the analysis using path analysis obtained the following results: transformational leadership, organizational culture and organizational commitment partially affect achievement motivation. Organizational culture, organizational commitment, and achievement motivation partially affect the performance of lecturers, while transformational leadership partially does not affect the performance of lecturers. Motivation acts as a variable mediating the influence of transformational leadership, organizational culture and organizational commitment on lecturer performance. The implication of this research is that there is a need for great attention to the achievement motivation of lecturers as the main factor that affects the performance of lecturers.